Oral health problems facing refugees in Europe: a scoping review - Eiad Zinah; Heba M. Al-Ibrahim (BMC, 2021)
Abstract Introduction Europe has been experiencing a flow of refugees and asylum seekers driven by conflicts or poverty. Their oral health is often neglected despite its clear impact on quality of life. Objective To explore the status of oral health among refugees and asylum seekers groups by examining the available literature and to determine which evidence exists regarding the problems they face in terms of oral health. Methods The current paper followed PRISMA guidelines. A scoping review methodology was followed to retrieve 2911 records from five databases and grey literature. Twelve articles met the following inclusion criteria: experimental research concentrated on the oral and dental health of refugees and/or asylum seekers between 1995 and 2020 in English. Analysis was both descriptive and thematic, whilst a critical appraisal was applied using the Critical Appraisal Skills Program (CASP). Results Seven studies (58,3%) were quantitative, while five studies (41,6%) were qualitative. In general, the quality of most of the studies (83.3%) was good. Limited access to oral health care services was shown with a higher prevalence of oral diseases compared to the native populations of the host countries. Approaches to improve oral health have been implemented in some studies and have shown positive outcomes. Conclusions Oral health care strategies should consider the oral health problems facing refugees in Europe, and oral health promotion campaigns are essential to give adequate guidance on how to access oral health care in the host countries.